Lipoprotein(a) levels are not independently associated with endogenous steroid hormone levels, in contrast to other non-genetic and genetic factors: the population-based SKIPOGH study. (14th October 2021) - Tessitore, E; Dobretz, K; Dhayat, N A; Estoppey, S; Kern, I; Ponte, B; Pruijm, M; Vogt, B; Vuilleumier, N; Bochud, M; Mach, F; Ehret, G
Abstract: Introduction: Lipoprotein(a) [Lp(a)] is an LDL-like molecule that is likely causally related to cardiovascular events. Lp(a) levels are highly variable, by more two orders of magnitude, and most of this variability appears to be of genetic origin. Exogenous hormones (hormone replacement therapy) seem to influence Lp(a) levels, but the impact of the variation of endogenous hormone levels on Lp(a) is unknown. Purpose: To investigate the association between Lp(a) levels and non-genetic factors, as endogenous steroid hormone levels, in contrast to genetic factors. Methods: We investigated the association of 28 endogenous steroids with Lp(a) levels and compared the association to other non-genetic and genetic variables in a prospective, population-based sample (N=1, 021). Results: The average age of the participants was 51 years and 53% were female. Median Lp(a) levels were 62 (±204) mg/l and the 90th and 99th percentile of Lp(a) was 616mg/l and 1035 mg/l respectively. The prevalence of a Lp(a) elevation ≥700mg/l was 3.2% and Lp(a) varied greatly from undetectable to 1, 690mg/l. Age explained 2.0% of Lp(a) variability (p<0.001), 1% was explained by LDL levels (p=0.001), and 40% by two single nucleotide polymorphisms near the Lp(a) gene that have been previously described. Lp(a) levels were on average almost two times more elevated in secondary prevention and in individuals with very elevated LDL levels (≥4.9 mmol/l). Of the 28 endogenous steroid hormones assessed, 5-androstene-3b, 16α, 17β-triol, androsterone, 16α-hydroxy DHEA, and estriol were nominatively associated with serum Lp(a) levels and explained 0.4–1% of Lp(a) variability in univariate analyses, but they did not reach significance in multi-variate models. Conclusion: Our results confirm previous findings demonstrating that the majority of the Lp(a) variation in the general population is of genetic origin. Age and LDL-levels explain a further small part of Lp(a) variability. Endogenous hormone levels do not contribute significantly to the wide range of variability. FUNDunding Acknowledgement: Type of funding sources: None.